Education Innovation: Collaboration between the Merdeka Curriculum and the Madrasah Diniyah-based Curriculum to Form Holistic Students - Sari, Frisca Nur; Rif'ah, Maziyya Naila; Aminah, Siti Aminah (JUPE : Jurnal Pendidikan Mandala, 2024)
The current learning process tends to focus more on cognitive aspects, such as mastery of theory, while the development of practical skills (psychomotor) and attitudes (affective) remains less optimal. Therefore, solutions are needed to address this issue. The purpose of this study is to describe educational innovation through the collaboration of the "Merdeka" curriculum and a distinctive curriculum based on madrasah diniyah to shape holistic students. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving school principals, vice principals for curriculum, and teachers. The focus of this study is on the planning, implementation, and challenges of the collaboration between the "Merdeka" curriculum and the distinctive curriculum based on madrasah diniyah to shape holistic students. The results show that the collaboration between the "Merdeka" curriculum and the distinctive curriculum based on madrasah diniyah is highly relevant for implementation as it successfully addresses students' competency gaps in psychomotor, affective, and cognitive aspects while supporting the goals of holistic education.